From “Union Power” to De-unionisation: Explaining the Rise and Fall of Trade Unionism in Western Australia’s Pilbara Iron Ore Industry and its Consequences - Vassiley, Alexis (Curtin University, 2020)
This thesis examines the rise and fall of trade unionism in Western Australia’s Pilbara iron ore industry from 1965 to 1999, and its consequences for today. The Marxist theory of the trade union bureaucracy and rank and file is critically applied and developed. This qualitative, case study research generates insights with respect to union strategy, union renewal and intra-union relations of broader significance than the Pilbara region itself.